VERMIWASH-A LIQUID BIOFERTILIZER - ., SHWETA; YADAV, A.K.; KUMAR, KIRAN; SHARMA, MAMTA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2005)
Vermiwash is a transparent pale yellow liquid biofertilizer. It is a mixture of excretory products and mucous secretion of earthworms and organic micronutrients of soil, which may be promoted as a potent fertilizer for better growth and yield of plants.